Test debts identification in a test factory - Aragão, Bruno Sabóia; de Castro, Rute Nogueira Silveira; Santos, Ismayle de Sousa; Lelli, Valéria; Andrade, Rossana Maria de Castro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Testing processes are commonly used with the aim of systematizing testing activities within a software development project or in a Test Factory (TF). However, even using a process, the team may fail to perform testing activities, intentionally or not, in order to, for example, make a faster delivery. In this situation, the team may incur a Technical Debt (TD): technical commitment generated during the software development lifecycle that may be beneficial in the short term, but in the long term, may be detrimental to the quality of the project. These TDs should be identified and managed, because if they remain invisible and non-refunded, they may accumulate incrementally and hinder, or even make impossible, maintenance tasks and software evolution. In this context, this work aims to report the experience of identifying technical test debts in a Test Factory. As object of the study, Test Debts were analyzed in five projects with the industry, in 2017, 2018 and 2019. As a result, four Test Debts causes were identified over the three years of our experience in the industry. Also, we present 11 lessons learned that help to identify and prevent Test Debts.